2018
DOI: 10.1177/2056305118763349
|View full text |Cite
|
Sign up to set email alerts
|

Time Collapse in Social Media: Extending the Context Collapse

Abstract: Unlike the typically anonymous online social environments of the 1990s, characterized by a nickname culture and a freedom to engage in changing identity games (Bechar-Israeli, 1995), modern social media profiles are often non-anonymous, with users revealing their real offline identities (Zhao, Grasmuck, & Martin, 2008). While Facebook and Google+ enforce real-name policies that require users to use their real names, Twitter and Instagram do not impose strict namerelated rules. Still, many users choose to discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 28 publications
3
36
0
3
Order By: Relevance
“…In this study, we focus primarily on how young adults have experienced Twitter, Facebook and Instagram over time because these are the most used social media platforms. We further label the young adults who participated in this study as social media natives (Brandtzaeg & Lüders, 2018;Brandtzaeg, 2016) because they have uploaded and published content on these social media since they were young teenagers. As such, these young adults represent the first generation that has experienced the important transition from youthful student to professional not only offline but also online, which makes them an important group to study.…”
Section: Definitions Of Conceptsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, we focus primarily on how young adults have experienced Twitter, Facebook and Instagram over time because these are the most used social media platforms. We further label the young adults who participated in this study as social media natives (Brandtzaeg & Lüders, 2018;Brandtzaeg, 2016) because they have uploaded and published content on these social media since they were young teenagers. As such, these young adults represent the first generation that has experienced the important transition from youthful student to professional not only offline but also online, which makes them an important group to study.…”
Section: Definitions Of Conceptsmentioning
confidence: 99%
“…This take on the lowest common denominator may even be more relevant in contemporary social media, which store searchable traces of people's social lives and their expressions of online self-presentation Running head: From Youthful Experimentation to Professional Identity 10 10 over time, from youth to adulthood. Facebook, for example, encourages users to be nonanonymous and to have a persistent identity over time (Brandtzaeg & Lüders, 2018).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, social media, such as Facebook, perpetuate the experience of linearity by confronting people with a chronological structure and showing them 'memories' from the past. Brandtzaeg and Lüders [68] found that this confrontation causes a "time collapse" in which young people feel embarrassed by their seemingly 'younger' selves. On the other hand, youths act upon these structural forces as cultural agents and have proven to be highly influential in how society and technology takes shape [11].…”
Section: Discussion: Taking Into Account the Cultural Construction Ofmentioning
confidence: 99%